Development of a new approach based on midwave infrared spectroscopy for post-consumer black plastic waste sorting in the recycling industry - Rozenstein, Offer (Waste management (New York, N.Y.), 2017)
Copyright © 2017 Elsevier Ltd. All rights reserved.